Utilization of bottom ash waste as a granular column to enhance the lateral load capacity of soft kaolin clay soil - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Wan Nur Syafiqah, Wan Jusoh (Springer, 2023)
Implementation of industrial wastes such as bottom ash in ground improvement can be cost-effective and environment-friendly. Ground improvement is an effective method of mitigation to improve problematic soils including soft kaolin clay soils as the problematic soils always expose to the severe settlements, low shear strength, immoderate plasticity, greater compressibility, dispersivity, bulging, erodibility, and susceptibility to climatic variables. Several studies conducted on the granular column using the bottom ash column. However, only a few studies have reported findings coherent with the statistical analysis. In this study, the lateral load capacity of bottom ash column-kaolin clay has been conducted. Coherently, the reinforced kaolin clay samples were tested via particle size distribution, Atterberg limit test, relative density, compaction test, permeability test, unconfined compression test, and unconsolidated undrained triaxial test with the single and group of encapsulated bottom ash columns with the geotextile encasement and a prediction model was developed. The effect of a number of columns, column diameter, column height, area replacement ratio, height penetration ratio, height-diameter column ratio, volume replacement ratio, and confining pressures on the shear strength of the single and group of encapsulated bottom ash columns have been investigated. The findings showed the effectiveness of using the bottom ash columns at various number of column, column diameter, column height, area replacement ratio, height penetration ratio, height-diameter column ratio, volume replacement ratio, and confining pressures can enhance the shear strength of the soil up to 77.00% at the optimal utilization of single encapsulated bottom ash column of 10-mm diameter and 80-mm height. Therefore, the study proved that the utilization of bottom ash waste as a granular column can significantly enhance the lateral load capacity of soft kaolin clay soil.